Mechanics of transfer printing for elastomeric stamps with collapse cavities. (May 2023) - Zhang, Yixing; Lu, Taiping; Zhao, Jinsheng; Ai, Jun; Chen, Yihao; Shi, Mingxing; Ma, Yinji; Feng, Xue
Abstract: Transfer printing technology provides an effective solution for manufacturing flexible electronic devices, enabling efficient, large-scale pick of film components from the donor substrate to the receiver substrate. Traditional transfer printing needs additional external stimuli, such as magnetic field, temperature, laser, or droplets. Here the elastomeric stamps with cavities are proposed to control adhesion. The cavities with and without collapse lead the elastomeric stamps to have different adhesion, which can be controlled by transfer printing pressure without additional external stimuli. A theoretical analysis model with the energy method is presented for the mechanism of the cavity stamp adhesion in the transfer printing process. With the guidance of this analytical model, the maximum pull-off force between the stamp and the film can be estimated. The effect of the stamp geometrical parameters on the interface adhesion force was evaluated in this article. The analytical predictions agree well with the experiments. These results can reveal systematic fundamental mechanisms and reversibly guide the optimization of geometries for stamp design assistance with transfer printing.